The Effect of Product Quality, Price and Sales Location of Nugin Lamping Tofu on Consumer Satisfaction - Mia Nur Yanti; Mutia Intan Savitri Herista (Riviera Publishing, 2024)
Tofu lanting nuggets are one type of snack food that is very popular with the public. Along with increasing consumer awareness of product quality, competition in the lanting tofu market is getting tougher. The focus of the study aims to determine the extent to which